Analytical studies on the antioxidant activity and beta glucan content of maitake mushrooms(grifola frondosa ) - ERDOĞAN, GÜLBİN (My University, 2021)
It is considered as a rnusluoom with brQad therapeutic properties, having potential biological effects such as antiturnor, antioxidant activities, high cholesterol, immunomodulatory, antihypeftensive, antidiabetic, cancer therapy and antilipenlic. Maitake rnushrooms and the maitake D-fractiorr prepared from them include a type of polysacchalide called beta glucan. Beta glucans stirnulatg the immune system and attack cancer; macrophages, T-cells, natural killer cells, and interleukin 1 and p. lt has been found that the polysacchalides in the structure of Maitake mnshrooms have a very large mplecular weight. Maitake mushroorns can be found in ma4y ways in the food market. The preferred fonns for use here in are the maitake rnushrooms, in the form ofliquid extracts, the n-raitake mnshroom in the forrn of capsules and tl-re maitake mushroorn in the form of tea. The aim of this study is to ereate a reView gontaining up-to-date information about the antioxidant propefiies of Maitake mushroom(Grifulafrontlosa), its polysaccharides and analytical methods used in the detemination of beta slucan.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Analitik Kimya; Sağlık Bilimleri; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Analytical Chemistry; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Yaşam Bilimleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Life Sciences; Maitake mushroom; beta glqcan; antioxidant; immune systern; anticancer.